The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/s0006-3495(96)79715-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear propagation of spherical calcium waves in rat cardiac myocytes

Abstract: Spontaneous calcium waves in enzymatically isolated rat cardiac myocytes were investigated by confocal laser scanning microscopy (CLSM) using the fluorescent Ca2+-indicator fluo-3 AM. As recently shown, a spreading wave of enhanced cytosolic calcium appears, most probably during Ca2+ overload, and is initiated by an elementary event called a "calcium spark." When measured by conventional fluorescence microscopy the propagation velocity of spontaneous calcium waves determined at several points along the cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
(43 reference statements)
5
29
0
Order By: Relevance
“…Therefore the ratio of transverse-to-longitudinal wave propagation velocity should be 7.9/0.8 to 17.1/1.8 (respectively) or 1.04, i.e., close to unity. This idea may explain the paradoxical observation that Ca 2ϩ waves are nearly spherical (21,22), despite the underlying Ca 2ϩ diffusion being asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the ratio of transverse-to-longitudinal wave propagation velocity should be 7.9/0.8 to 17.1/1.8 (respectively) or 1.04, i.e., close to unity. This idea may explain the paradoxical observation that Ca 2ϩ waves are nearly spherical (21,22), despite the underlying Ca 2ϩ diffusion being asymmetric.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we have identified a specific sequence of three amino acids within the cytoplasmic region of Fc␥RIIA that controls the calcium wave pathway within living cells and, crucially, the ability of immune cells to destroy internalized targets via phagolysosome formation. Previous studies have identified calcium waves in certain cell types including oocytes, myocytes, and retinal pigment epithelial cell monolayers (23)(24)(25). To observe waves in smaller cells, we have developed methods to collect movies of traveling chemical waves in cells by using brief shutter speeds (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…The cytosol is the medium surrounded by the cell membrane, in which the cell organelles are embedded. Intracellular calcium waves were first observed in medaka eggs [4] and later on in Xenopus oocytes [5,6], hepatocytes [7], articular chondrocytes [8], and cardiac myocytes [9,10]. The local dynamics inside these cells is nonlinear release and uptake of Ca 21 from intracellular stores like the endoplasmatic reticulum (ER) and the mitochondria.…”
Section: (Received 1 November 1999)mentioning
confidence: 99%